Cross Cultural Meta-analysis of Personality and Leadership Effectiveness and Evaluation of Changes Over Time - (:unkn) unknown (My University, 2017)
The research integrates and expands upon trait theory and culturally-endorsed leadership theory by performing a meta-analysis of the big five personality traits relationships with leadership effectiveness through a cultural and temporal lens. Using only organizational and military/government samples, this investigation delivers three important contributions; corroborates support for trait theory, reveals trait variability, and identifies trends in global leadership. In order to be a “Great Man”, a person needs to be born with the right traits at the right time in the right place. Consistent with prior meta-analytical research, big five traits consistently predicted leadership effectiveness, further supporting trait theory. While all traits demonstrated variability by culture and time, agreeableness and extraversion were most pronounced. Germanic and Confucian cultures produced uniquely different results for extraversion. Agreeableness appeared culturally consistent, and not only increased over time, but also produced two distinctly different time periods. Culturally-endorsed leadership theory may explain these outcomes. Results are discussed with respect to cultural convergences, globalization and the nascent field of global leadership.
Keywords: Culture; Leadership; Meta-Analysis; Personality; Time